Reviewer Acknowledgements for Journal of Agricultural Studies, Vol. 10, No. 3 - Williams, Richard (Journal of Agricultural Studies, 2022)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 10, Number 3 Alessandra M. Lima Naoe, Federal University of Tocantins, Brazil Alexandru Ioan Apahidean, Univ. of Agricultural Sciences and Veterinary Medicine, Romania André Luiz Rodrigues Magalhães, UFAPE, Brazil Angel Ramon Sanchez Delgado, Universidade federal Rural do Rio de Janeiro, Brazil Arnaud Z. Dragicevic, IRSTEA, France Azwimbavhi Reckson Mulidzi, Agricultural Research Council, South Africa Darwin Pangaribuan, University of Lampung, Indonesia Eliana Mariela Werbin, National University of Cordoba, Argentinian Eric Owusu Danquah, CSIR-Crops Research Institute, Ghana Fernando Rodrigues de Amorim, State University of Paulista (UNESP), Brazil Guitong Li, China Agricultural University, China Habu Saleh Hamisu, National Horticultural Research Institute, Nigeria Hedayatollah K. Soureshjani, Ferdowsi University of Mashhad, Iran Jorge A. López, University Tiradentes, Brazil Mahyar Gerami, Sana Institute of Higher Education, Iran Nkemkanma Vivian Agi, Rivers State University Port Harcourt, Nigeria Olga Mykhailenko, National University of Pharmacy, Ukraine Raul Pașcalău, Banat's University, Romania Shakirudeen Abimbola Lawal, University of Cape Town, South Africa Shubha Kumari, ICAR-RCER, India Somaia Alkhair, Alzaeim Alazhari University, Sudan Sudu Hakuruge Pushpa Malkanthi, Sabaragamuwa University of Sri Lanka, Sri Lanka Sybelle Mesquita Silva, Universidade Federal de Alagoas, Brazil Zakaria Fouad Abdallah, National Research Centre, Egypt Richard Williams Editorial Assistant Journal of Agricultural Studies -------------------------------------- Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org